Double blind, randomised, placebo controlled, crossover, multicentre study to determine the efficacy of a 0.1% (w/v) sodium hyaluronate solution (Fermavisc) in the treatment of dry eye syndrome - Condon, Patrick I; McEwen, Charles G; Wright, Mark; Mackintosh, Graeme; Prescott, Robin J; McDonald, Carolyn (British journal of ophthalmology, 1999)
BACKGROUND/AIMS Hyaluronan (sodium hyaluronate) has been shown to confer objective and subjective improvement in patients with dry eye syndrome. This study compared the efficacy and safety of a 0.1% solution of hyaluronan with 0.9% saline, when administered topically to the eye, in the treatment of symptoms of severe dry eye syndrome. METHODS A randomised, double blind, crossover clinical trial in which subjects were randomised to receive either hyaluronan or saline, applied as one or two drops to the eye, three or four times a day or as required. After 28 days’ treatment, subjects crossed over to the other study medication for a further 28 days’ treatment. RESULTS 70 subjects were included in the analyses of efficacy and significant improvements in Schirmer’s score (p=0.0006) and rose bengal staining score (p=0.0001) were observed during treatment with hyaluronan. In a subjective assessment of the effectiveness of two treatments, a majority of subjects felt that hyaluronan was more effective than saline in alleviating the symptoms of burning and grittiness (p<0.001). No adverse events attributable to hyaluronan treatment were reported. CONCLUSION The study demonstrates a clear benefit of hyaluronan over saline, in both subjective and objective assessments of dry eye syndrome. Hyaluronan was shown to be well tolerated.